Modeling Service Quality Improvement Priorities in Selected Hotels for Efficient Service Delivery - Tukamushaba, Eddy K.; Musinguzi, Dan; Katongole, Celestine; Xiao, Honggen (International Journal of Tourism Sciences, 2012)
This paper develops an integrated performance model that is aimed at improving service quality and providing accurate indicators that guide hotel managers in improving service priorities that promote customer satisfaction and eliminate resource wastage. The study was guided by three objectives of determining the level of importance of selected service quality attributes the level of satisfaction with selected service quality attributes and establishing the key service quality attributes that aid managers focus their improvement efforts. Quantitative techniques were used based on a sample size of 238 respondents selected from 30 hotels labeled as Common wealth Heads Of Government Meeting hotels in 2007. The findings indicate that out of the 22 service quality items, 13 needed
Keywords: Service quality; Customer satisfaction; Performance management